Nanomaterials-Mediated Therapeutics and Diagnosis Strategies for Myocardial Infarction - Lv, Qingbo; Ma, Boxuan; Li, Wujiao; Fu, Guosheng; Wang, Xiaoyu; Xiao, Yun (Frontiers in Chemistry, 2022)
The alarming mortality and morbidity rate of myocardial infarction (MI) is becoming an important impetus in the development of early diagnosis and appropriate therapeutic approaches, which are critical for saving patients’ lives and improving post-infarction prognosis. Despite several advances that have been made in the treatment of MI, current strategies are still far from satisfactory. Nanomaterials devote considerable contribution to tackling the drawbacks of conventional therapy of MI by improving the homeostasis in the cardiac microenvironment via targeting, immune modulation, and repairment. This review emphasizes the strategies of nanomaterials-based MI treatment, including cardiac targeting drug delivery, immune-modulation strategy, antioxidants and antiapoptosis strategy, nanomaterials-mediated stem cell therapy, and cardiac tissue engineering. Furthermore, nanomaterials-based diagnosis strategies for MI was presented in term of nanomaterials-based immunoassay and nano-enhanced cardiac imaging. Taken together, although nanomaterials-based strategies for the therapeutics and diagnosis of MI are both promising and challenging, such a strategy still explores the immense potential in the development of the next generation of MI treatment.